CHARACTERISTICS OF COASTAL AREA LICENSE MANAGEMENT IN THE PROVINCE OF BANGKA BELITUNG ISLANDS - Muhammad Syaiful Anwar; Rafiqa Sari; Ndaru Satrio (International Conference On Law And Social Sciences, 2024)
Coastal areas are related to the interests of regional governments and the interests of the central government regarding management, especially mining in coastal areas. Mining activities that occur in the Bangka Belitung Islands are not only on land but have also entered coastal areas. There is overlap in the authority to grant permits and there is environmental damage which must be accounted for by those carrying out mining activities. This research aims to determine the characteristics of granting mining permits in coastal areas based on regional autonomy rights and environmental law enforcement on coastal mining activities in the Bangka Belitung Islands region. This research uses normative legal research which takes a statutory and conceptual approach. The results of this research indicate that there is still overlapping authority rules for granting permits between the central government and regional governments in coastal areas based on the principle of regional autonomy and the characteristic mechanisms of environmental monitoring patterns that are more directed towards enforcement of administrative law but also the criminal dimension which is premium remidium.